Símbolos projetivos e ângulos de extinção - Salgado, Eduardo A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1962)
Using the "projective symbols" by Fedorow, it is possible to calculate the angles of extinction of the faces of a same zone, in relation to the axis of the zone, as it is demonstrated by the author.